Voting Behavior amongst South-Western States in Nigeria: A Study of Oyo and Osun States (2015-2019) - Michael, Ezedikachi Eze - (NIU Journal of Social Sciences, 2021)
The high degree of mistrust in the electoral process has affected the voting behaviour of voters during election in Nigeria. It is against this backdrop, that the study investigated the voting behavior among South-western states, using Oyo and Osun states respectively from 2015-2019. The study adopted quantitative method and employed survey research design. Data was generated through the administering of questionnaire. Data from journals, articles, books (published & unpublished), internet and documentaries complemented the major sources of data. Findings revealed that there are factors negating the voting behavior of electorates in South-western Nigeria. The study concluded that voting behaviour is an essential element in democratic system. However, in Nigeria, there is low level of participation of the electorates during elections because of high degree of mistrust in the electoral system. The study recommended that government should improve in areas of electoral process and be proactive by orientating citizens during elections. Keywords : Voting, Behaviour, Voting behaviour, South-western, States